The Impact Of The Development Of The Culture Of The Turan Peoples On World Civilization - Xudоyаrоv Jаsur Sаpаrоvich (Zien Journals, 2025)
This article describes the transformation of the culture of the ancient Turanian peoples into world civilization, as well as the scholars who made a significant contribution to the development of Islam in Central Asia
Keywords: Ancient Turan; Central Asia; development